Manajemen Bencana Penanggulangan Pasca Banjir Di (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
ABSTRACTThis study aimed to find out the management of the post-flood postal disaster in North Luwu Regency which focused on the rehabilitation and reconstruction process. This study used qualitative research with a type of descriptive research, namely to describe and explain the management of post-flood prevention disasters in North Luwu Regency. The results of this study showed that the reconstruction process carried out by the North Luwu Regency BPBD was still not massive, due to the development of the infrastructure sector all of them were still in the stages of the proposal. While in the rehabilitation process of the North Luwu Regency BPBD only focused on activities such as repaired or cleaning houses of residents who were buried by mud material. The post-flood management disaster management in North Luwu Regency was not too optimal because the reconstruction process and rehabilitation carried out by the North Luwu Regency BPBD after the flood disaster was still in the proposal. Keywords: disaster management, post-flood prevention